Does The Sexual Violence The Fault Of Man Or The Fault Of Woman's Stupidity? When Religious Commodification and Offensive Marketing Go Hand in Hand - Kusumastuti, Retno Dyah; Istiyanto, S. Bekti (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
Religious commodification, especially Islamic commodification has been rampant in modern times. This phenomenon also emboldens brands with religious symbolism to conduct offensive marketing, namely Rabbani. This research further investigates the integration of religious commodification and offensive marketing conducted by the Rabbani brand. This research utilized a qualitative and descriptive approach through the case study of Rabbani offensive marketing. The findings of this research are Rabbani has benefitted from religious commodification practices. This in turn emboldens Rabbani to engage in offensive marketing by attacking Muslim women who did not wear the veil. This research implies that religious commodification could also bring a negative impact, especially if this practice is coupled with offensive marketing. Thus, consumers need to be more critical and not easily convinced by the offerings of products that rely on religious commodification, especially if these products use unethical marketing practices such as offensive marketing.